2010
DOI: 10.1097/nmd.0b013e3181e08685
|View full text |Cite
|
Sign up to set email alerts
|

Trauma and Current Posttraumatic Stress Symptoms in Elderly German Women Who Experienced Wartime Rapes in 1945

Abstract: The aim of this study was to determine the persistent trauma impact and significant posttraumatic stress symptoms in a sample of very elderly German women who survived the mass rapes committed by soldiers at the end of World War II. A total of 27 women were recruited, interviewed, and then administered a modified Posttraumatic Diagnostic Scale. They all reported a very severe degree of trauma exposure in 1945; 19% reported significant current posttraumatic stress symptoms indicating a possible posttraumatic st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
11
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 9 publications
2
11
0
2
Order By: Relevance
“…Sexual violence was experienced or witnessed by almost 13%, with a higher prevalence in the Soviet zone. This important topic (Kuwert & Freyberger, 2007; Kuwert et al, 2010) will be addressed elsewhere (Lueger-Schuster, Glück, Tran, & Zeilinger, 2012). In total, persons in our study reported less direct involvement in actions of war or experiences in combat zones (apart from bombing) than in other studies (Kuwert et al, 2007b; Maercker et al, 2008; Spitzer et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Sexual violence was experienced or witnessed by almost 13%, with a higher prevalence in the Soviet zone. This important topic (Kuwert & Freyberger, 2007; Kuwert et al, 2010) will be addressed elsewhere (Lueger-Schuster, Glück, Tran, & Zeilinger, 2012). In total, persons in our study reported less direct involvement in actions of war or experiences in combat zones (apart from bombing) than in other studies (Kuwert et al, 2007b; Maercker et al, 2008; Spitzer et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The displacement took place roughly between 1944 and 1947, and the refugees went mainly to the western parts of Germany. The displacement process was accompanied by an enormous amount of traumatic events, such as air raids, combat contact, wartime rapes, and others (Benz, 1985;Kuwert et al, 2010). A population-based survey of the German elderly general population (not differentiating between displaced and nondisplaced individuals) showed elevated levels of posttraumatic stress disorder (PTSD) associated with WW II trauma (Hauffa et al, 2011).…”
mentioning
confidence: 99%
“…Adapted from [48] matized patients [43]. From a lifespan perspective, sexual or physical abuse in early life is associated with psychopathology in later adulthood [29], especially the severity of somatization [41] and chronic pain [18]. Against the background of World War II, the extent and long-term effects of war-related traumatic experiences (e.g., experiences during military war service, bombing, or wartime rape) in the elderly generation are of special interest [36].…”
Section: Burden Of Traumatization Of Early War Experiencesmentioning
confidence: 99%